Characterization of Polycrystalline Materials Using Synchrotron X-ray Imaging and Diffraction Techniques - Ludwig, W; King, A; Herbig, M; Reischig, P; Marrow, J; Babout, L; Lauridsen, E; Proudhon, H; Buffiere, J (2010)
The combination of synchrotron radiation x-ray imaging and diffraction techniques offers new possibilities for in-situ observation of deformation and damage mechanisms in the bulk of polycrystalline materials. Minute changes in electron density (i.e., cracks, porosities) can be detected using propagation based phase contrast imaging, a 3-D imaging mode exploiting the coherence properties of third generation synchrotron beams. Furthermore, for some classes of polycrystalline materials, one may use a 3-D variant of x-ray diffraction imaging, termed x-ray diffraction contrast tomography. X-ray diffraction contrast tomography provides access to the 3-D shape, orientation, and elastic strain state of the individual grains from polycrystalline sample volumes containing up to thousand grains. Combining both imaging modalities, one obtains a comprehensive description of the materials microstructure at the micrometer length scale. Repeated observation during (interrupted) mechanical tests provide unprecedented insight into crystallographic and grain microstructure related aspects of polycrystalline deformation and degradation mechanisms. © 2010 TMS.